Exertional sodium loss does not increase immediate salt appetite or dietary sodium intake in athletes. (1st July 2021) - Manevitz, Zev; Leshem, Micah; Heled, Yuval; Epstein, Yoram; Gershon, Barak; Kodesh, Einat
Abstract : We tested whether salt preference increases immediately after exertion-induced Na + loss in sweat, and whether this may generalise to an increase in habitual dietary Na + intake. For the first aim, trained athletes (n = 20) exercised in 2 ambient temperatures and sweat Na + loss related to immediate salt preference assessed by taste, intake and psychophysical tests. For the second aim, we compared dietary and urinary Na +, and salt preference, seasoning and hedonics in the athletes and sedentary men (n = 20). No relationship was found between sodium loss during exercise and immediate preference for salt or psychophysical responses, and no differences in comparison to sedentary men. However, athlete diet had fewer foods (29.4 ± 1.5 vs 37.8 ± 1.9, p < 0.001), less seasoning (19 vs 32. p = 0.011) and more athletes reported dietary limitations (31 vs 11, p < 0.05), although nutrient content did not differ. Together these might suggest athlete adherence to a healthy diet at the expense of variety and flavour and a dissociation between dietary reports and intake. Athletes, more than controls, liked foods rich in energy and K + suggesting compensatory-driven hedonics, although overall their intake did not differ. The findings are consistent with the absence of a salt appetite responding to Na + loss in humans, and specifically that trained athletes do not increase their preference for salt in immediate response to exertion-induced Na + loss and are not at risk for increased dietary Na + compared to sedentary men.